Native valve endocarditis caused by E rysipelothrix Rhusiopathiae: presenting with refractory heart failure and requiring surgical valve replacement—report on a rare zoonosis - Altibi, Ahmed M (BMJ Case Rep, 2019)
Erysipelothrix Rhusiopathiae is a Gram-positive bacillus that is ubiquitous in nature. The bacterium is a zoonotic pathogen known to infect wild and domestic animals. Human infections, however, are uncommon and typically present with localised or generalised cutaneous lesions. Systemic infection in the form of bacteraemia with seeding to various organs is the least common form of the disease. Infections in humans tend to be associated with occupational exposure and close contact with animals. Clinical data of a 61-year-old male patient with Gram-positive bacilli bacteraemia and E. Rhusiopathiae-induced endocarditis are presented here. The patient presented with refractory congestive heart failure secondary to severe acute aortic regurgitation mandating surgical valve replacement. The described case has special clinical merit given the lack of fever and leukocytosis, absence of erysipeloid cutaneous manifestations and refractoriness to medical management. E. Rhusiopathiae should be considered in the differential diagnosis for Gram-positive bacilli bacteraemia and endocarditis. In the proper clinical setting, occupational exposure and animal contacts are helpful clues to raise suspicion for this bacillus. The high mortality associated with the pathogen should urge for early identification and initiation of antimicrobial treatment.